Psychiatric disorders among women with the fragile X premutation without children affected by fragile X syndrome. Issue 8 (12th September 2016) - Gossett, Amy; Sansone, Stephanie; Schneider, Andrea; Johnston, Cindy; Hagerman, Randi; Tassone, Flora; Rivera, Susan M.; Seritan, Andreea L.; Hessl, David
Abstract : Several studies have demonstrated increased rates of anxiety and depressive disorders among female carriers of the fragile X premutation. However, the majority of these studies focused on mothers of children with fragile X syndrome, who experience higher rates of parenting stress that may contribute to the emergence of these disorders. The present study compared psychiatric symptom presentation (utilizing measures of current symptoms and lifetime DSM‐IV Axis I disorders) in 24 female carriers without affected children (mean age = 32.1 years) to 26 non‐carrier women from the community (mean age = 30.5 years). We also examined the association between CGG repeat size (adjusted for X activation ratio) and mRNA, with severity of psychiatric symptoms. Women with the premutation reported significantly elevated symptoms of anxiety, depression, interpersonal sensitivity, obsessive‐compulsiveness, and somatization relative to controls during the past week. Carriers had significantly higher rates of lifetime social phobia (42.3%) compared to controls (12.5%); however, this comparison did not remain significant after multiple comparison adjustment. Rates of other psychiatric disorders were not significantly elevated relative to controls, though it should be noted that lifetime rates among controls were much higher than previously published population estimates. Although the sample is relatively small, the study of this unique cohort suggests the premutation confers risk for mood and anxiety disorders independent of the stress of parenting children with FXS. Screening for psychiatric disorders in women with the premutation, even before they become parents, is important and highly encouraged. © 2016 Wiley Periodicals, Inc.